Magnetic field of the classical Cepheid η Aql: new results. Issue Volume 9:Issue S302(2013) (7th August 2014) - Butkovskaya, V.; Plachinda, S.; Baklanova, D.; Butkovskyi, V.
Abstract: We present the results of the spectropolarimetric study of the classical Cepheid η Aql in 2002, 2004, 2010, and 2012. The longitudinal magnetic field of η Aql was found to be variable with the pulsation cycle of 7.176726 day. The amplitude, phase, and mean value of the field vary from year to year presumably due to stellar rotation or dynamo mechanisms.